PERALIHAN JAMINAN MELALUI SUBROGASI DALAM PERJANJIAN KREDIT MENURUT UNDANG-UNDANG NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN ATAS TANAH BESERTA BENDA-BENDA YANG BERKAITAN DENGAN TANAH: Cecep Supriyatna - admin, admin (Reformasi Hukum, 2018)
This study has the following objectives: (a) To obtain an explanation of the dispute resolution of collateral transfer through subrogation in a credit agreement; (b) To provide an overview of the legal protection of creditors on transfer of guarantees through subrogation;. The methods used is the normative yuridical. Research Results, (a). In the Subrogation process, the Bank will submit a Claim to the Guarantee Institution that covers the Credit Facility with the conditions specified in the cooperation agreement between the Secured Party and the Guarantee Institution. When the first payment occurs by the Debtor since the Claim is paid by the Guarantee Agency, Subrogation occurs; (b). Legal protection for creditors on transfer of collateral through subrogation in a credit agreement, whereby the Bank is a creditor that can be harmed due to default by the debtor by means of giving measured power in accordance with clear laws and regulations. Creditors have Claim Rights and Credit Rescue efforts as Legal Protection for Banks in Credit Settlement Through Subrogation